Electrode and battery

JP2025022950AActive Publication Date: 2025-02-14TOYOTA JIDOSHA KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024204517
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-14
Estimated Expiration
2042-01-13

AI Technical Summary

Benefits of technology

【0021】 本開示における電極は、抵抗低減と、サイクル特性向上とを両立できるという効果を奏する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022950000001_ABST
    Figure 2025022950000001_ABST
Patent Text Reader

Abstract

To provide an electrode that satisfies both resistance reduction and improvement of cycle characteristics.SOLUTION: Provided is an electrode used in a battery, where the electrode has an electrode current collector and an electrode active material layer, the electrode active material layer contains an electrode active material of a single crystal system and an electrode active material of a polycrystal system as an electrode active material, the electrode active material of the single crystal system and the electrode active material of the polycrystal system are lithium transition metal composite oxide, the electrode active material layer has a first layer including a first surface on the opposite side of the electrode current collector and a second layer including a second surface on the electrode current collector side, the first layer contains the electrode active material of the single crystal system as a main component of the electrode active material, and the second layer contains the electrode active material of the polycrystal system as a main component of the electrode active material.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrode and a battery. [Background technology]

[0002] In recent years, with the rapid spread of electronic devices such as personal computers and mobile phones, the development of batteries to be used as power sources for these devices is progressing. In the automotive industry, the development of batteries to be used in hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs) and battery electric vehicles (BEVs) is also progressing. Among various types of batteries, lithium-ion secondary batteries have the advantage of having a high energy density.

[0003] A battery, such as a lithium ion secondary battery, usually has a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode. The positive electrode usually has a positive electrode current collector and a positive electrode active material layer containing a positive electrode active material. The negative electrode usually has a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material.

[0004] For example, Patent Document 1 discloses a positive electrode active material for a non-aqueous secondary battery, which is composed of primary particles that are mainly composed of nickel and lithium, are single crystals, and have an average particle size of 2 to 8 μm. Patent Document 2 discloses a method for preparing a powdered positive electrode active material, which includes a first compound powder containing polycrystalline particles and a second compound powder containing single crystal monolithic particles. Patent Document 3 discloses that a separator contains, as a heat-resistant material, polycrystalline particles formed by connecting single crystal primary particles. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-054159 A [Patent Document 2] Special Publication No. 2021-507486 [Patent Document 3] JP 2012-084255 A Summary of the Invention [Problem to be solved by the invention]

[0006] For example, when a single crystal electrode active material is used as in Patent Document 1, the resistance of the electrode active material layer is likely to be high. On the other hand, when a single crystal electrode active material and a polycrystalline electrode active material are mixed and used as in Patent Document 2, current tends to concentrate in the polycrystalline electrode active material, which has low resistance, and cycle characteristics tend to deteriorate.

[0007] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide an electrode that achieves both reduced resistance and improved cycle characteristics. [Means for solving the problem]

[0008] The present disclosure provides an electrode for use in a battery, the electrode having an electrode current collector and an electrode active material layer, the electrode active material layer containing, as electrode active materials, a single crystal electrode active material and a polycrystalline electrode active material, the single crystal electrode active material and the polycrystalline electrode active material being each a lithium transition metal composite oxide, the electrode active material layer having a first layer including a first surface on a side opposite to the electrode current collector and a second layer including a second surface on the electrode current collector side, the first layer containing the single crystal electrode active material as a main component of the electrode active material, and the second layer containing the polycrystalline electrode active material as a main component of the electrode active material.

[0009] According to the present disclosure, by using a single crystal electrode active material for the first layer and a polycrystalline electrode active material for the second layer, an electrode that achieves both reduced resistance and improved cycle characteristics is obtained.

[0010] In the above disclosure, the single crystal electrode active material and the polycrystalline electrode active material may each contain at least one of Ni, Co, and Mn as a transition metal.

[0011] In the above disclosure, the constituent elements constituting the single crystal electrode active material and the constituent elements constituting the polycrystalline electrode active material may be the same.

[0012] In the above disclosure, the first layer may contain the polycrystalline electrode active material.

[0013] In the above disclosure, the first layer does not need to contain the polycrystalline electrode active material.

[0014] In the above disclosure, the second layer may contain the single crystal electrode active material.

[0015] In the above disclosure, the second layer does not need to contain the single crystal electrode active material.

[0016] In the above disclosure, the first layer may contain a first composite in which a fibrous carbon material is adhered to a surface of the monocrystalline electrode active material, and the second layer may contain a second composite in which a particulate carbon material is adhered to a surface of the polycrystalline electrode active material.

[0017] In the above disclosure, the fibrous carbon material may be carbon nanotubes, and the particulate carbon material may be carbon black.

[0018] In the above disclosure, the electrode may be a positive electrode.

[0019] The present disclosure also provides a battery having a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode, wherein at least one of the positive electrode and the negative electrode is the electrode described above.

[0020] According to the present disclosure, at least one of the positive electrode and the negative electrode is the above-mentioned electrode, and therefore the battery achieves both reduced resistance and improved cycle characteristics. Effect of the Invention

[0021] The electrode according to the present disclosure has an effect of achieving both reduced resistance and improved cycle characteristics. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. [Diagram 2] FIG. 2 is an explanatory diagram illustrating an electrode active material layer in the present disclosure. [Diagram 3] FIG. 2 is an explanatory diagram illustrating an electrode active material layer in the present disclosure. [Figure 4] FIG. 2 is a flow diagram showing a method for synthesizing a positive electrode active material in a synthesis example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, the electrodes and batteries of the present disclosure will be described in detail. In this specification, when expressing an aspect in which a certain member is disposed on another member, the term "on" simply refers to both a case in which the other member is disposed directly on the certain member so as to be in contact with the certain member, and a case in which the other member is disposed above the certain member via another member, unless otherwise specified.

[0024] A. Electrode The electrodes in the present disclosure are used in batteries. FIG. 1 is a schematic cross-sectional view illustrating a battery in the present disclosure. The battery 100 shown in FIG. 1 has a positive electrode 10, a negative electrode 20, and an electrolyte layer 30 disposed between the positive electrode 10 and the negative electrode 20. The positive electrode 10 has a positive electrode current collector 1 and a positive electrode active material layer 2 disposed between the positive electrode current collector 1 and the electrolyte layer 30. On the other hand, the negative electrode 20 has a negative electrode current collector 11 and a negative electrode active material layer 12 disposed between the negative electrode current collector 11 and the electrolyte layer 30. The electrodes in the present disclosure may be a positive electrode, a negative electrode, or both a positive electrode and a negative electrode.

[0025] FIG. 2 is an explanatory diagram for explaining an electrode active material layer in the present disclosure. FIG. 2 illustrates a case where the electrode active material layer is a positive electrode active material layer. The positive electrode active material layer 2 contains a single crystal electrode active material and a polycrystalline electrode active material as positive electrode active materials. The definitions of these will be described later. The single crystal electrode active material and the polycrystalline electrode active material are each a lithium transition metal composite oxide.

[0026] As shown in FIG. 2, the positive electrode active material layer 2 is disposed on a first surface S 1 and a second surface S on the positive electrode current collector (not shown) side. 2 and a second layer 22 containing the same. As shown in FIG. 3, the positive electrode active material layer 2 may or may not have one or more intermediate layers 23 between the first layer 21 and the second layer 22. The first layer 21 contains a single crystal positive electrode active material as the main component of the positive electrode active material. On the other hand, the second layer 22 contains a polycrystalline positive electrode active material as the main component of the positive electrode active material.

[0027] According to the present disclosure, by using a single-crystal electrode active material for the first layer and a polycrystalline electrode active material for the second layer, an electrode that achieves both reduced resistance and improved cycle characteristics is obtained. As described above, when a single-crystal electrode active material is used, the resistance of the electrode active material layer is likely to be high. This is because the crystallite diameter of a single-crystal electrode active material is usually larger than that of a polycrystalline electrode active material. Specifically, the larger the crystallite diameter, the greater the influence of the inside of the particle where electrode reaction is difficult to occur, and the higher the resistance is likely to be. In addition, as described above, when a single-crystal electrode active material and a polycrystalline electrode active material are mixed and used, current is concentrated in the polycrystalline electrode active material with low resistance, and local deterioration is likely to occur. Therefore, the cycle characteristics are likely to be reduced.

[0028] In contrast, in the present disclosure, a single-crystal electrode active material is used in the first layer, and a polycrystalline electrode active material is used in the second layer. In the first layer, for example, a single-crystal electrode active material with lower reactivity (higher stability) is used because it reacts more with Li that has moved from the electrolyte layer during charging. As a result, cycle characteristics are improved. On the other hand, in the second layer, for example, a polycrystalline electrode active material with lower resistance is used because the movement distance of Li during charging is long and resistance is likely to increase. In this way, by using a single-crystal electrode active material in the first layer and a polycrystalline electrode active material in the second layer in consideration of the stability to Li and the movement distance of Li, it is possible to achieve both resistance reduction and improvement of cycle characteristics.

[0029] 1. Electrode active material layer The electrode active material layer in the present disclosure contains, as electrode active materials, a single crystal electrode active material and a polycrystalline electrode active material, and has a first layer including a first surface on the side opposite to the electrode current collector, and a second layer including a second surface on the electrode current collector side.

[0030] (1) Electrode active material The electrode active material in the present disclosure may be a positive electrode active material or a negative electrode active material. The electrode active material layer contains a single crystal electrode active material and a polycrystalline electrode active material as the electrode active material. The shape of the single crystal electrode active material and the polycrystalline electrode active material is usually particulate. In the present disclosure, the "single crystal electrode active material" refers to an electrode active material having a primary particle diameter of 1.5 μm or more. In particular, the primary particle diameter of the single crystal electrode active material is preferably 2.0 μm or more and 6.0 μm or less. On the other hand, in the present disclosure, the "polycrystalline electrode active material" refers to an electrode active material having a primary particle diameter of less than 1.5 μm. In particular, the primary particle diameter of the polycrystalline electrode active material is preferably 0.5 μm or more and less than 1.0 μm. The primary particle diameter refers to the diameter (longest diameter) of the primary particle, and is determined from an image obtained by observation with a scanning electron microscope (SEM). A primary particle is a particle that corresponds to a unit particle (ultimate particle) judging from the geometric form observed by SEM. A unit particle is typically a crystallite (single crystal). Single crystals include not only ideal perfect crystals but also crystals having lattice defects. Single crystal-based electrode active materials also include those in which a relatively small number of single crystals (for example, 20 or less, which may be 10 or less, or 5 or less) are bonded together. On the other hand, polycrystalline electrode active materials are usually those in which a large number of single crystals (for example, more than 20, which may be 100 or more) are bonded together without any regularity (randomly).

[0031] The single crystal electrode active material in the present disclosure is a lithium transition metal composite oxide. 1 (M 1 is one or more transition metals) and O. 1 Examples of the transition metal include Ni, Co, Mn, Ti, V, Cr, Fe, Cu, and Zn. Among them, it is preferable that the single crystal electrode active material contains at least one of Ni, Co, and Mn as the transition metal. 1may be partially substituted with a metal (including metalloid) belonging to Groups 13 to 17 of the periodic table. A typical example of a metal belonging to Groups 13 to 17 of the periodic table is Al.

[0032] A specific example of a single crystal electrode active material is LiCoO 2 , LiMnO 2 , LiNiO 2 , Li(Ni,Co,Mn)O 2 , Li(Ni,Co,Al)O 2 Rock salt layered active materials such as LiMn 2 O 4 , Li(Ni 0.5 Mn 1.5 )O 4 , Li 4 Ti 5 O 12 Spinel-type active materials such as LiFePO 4 , LiMnPO 4 , LiNiPO 4 , LiCoPO 4 Examples of the olivine type active material include those mentioned above.

[0033] The polycrystalline electrode active material in the present disclosure is a lithium transition metal composite oxide. 2 (M 2 is one or more transition metals) and O. 2 Examples of the transition metal include Ni, Co, Mn, Ti, V, Cr, Fe, Cu, and Zn. Among them, it is preferable that the polycrystalline electrode active material contains at least one of Ni, Co, and Mn as the transition metal. 2 A part of the transition metal M 1 Similarly, it may be substituted with a metal (including metalloid) belonging to groups 13 to 17 of the periodic table. Specific examples of polycrystalline electrode active materials are also the same as the specific examples of the single crystal electrode active materials described above.

[0034] It is preferable that the constituent elements constituting the single crystal electrode active material and the constituent elements constituting the polycrystalline electrode active material are the same. For example, when the single crystal electrode active material contains Li, Ni, Co, Mn, and O as constituent elements, it is preferable that the polycrystalline electrode active material also contains Li, Ni, Co, Mn, and O as constituent elements. It is also preferable that the composition of the single crystal electrode active material and the composition of the polycrystalline electrode active material are the same. For example, when the single crystal electrode active material contains LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 When the composition is LiNi, the polycrystalline electrode active material is also 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 It is preferable that the composition of the above formula is as follows:

[0035] For example, when a single crystal electrode active material and a polycrystalline electrode active material contain Li, Ni, Co, Mn, and O as constituent elements, respectively, a typical peak appears at 2θ=18.5° to 19.0° in X-ray diffraction (XRD) using CuKα radiation. The half-width (full width at half maximum) of the peak is Hw, and Hw in the single crystal electrode active material is Hw1, and Hw in the polycrystalline electrode active material is Hw2. Hw1 is usually smaller than Hw2. Hw1 may be, for example, 0.8° or less. On the other hand, Hw2 may be, for example, larger than 0.8°.

[0036] (2) First layer The first layer in the present disclosure is a layer including a first surface of the electrode active material layer on the side opposite to the electrode current collector. The first surface is usually the surface of the electrode active material layer on the electrolyte layer side. The first layer contains a single-crystal electrode active material as a main component of the electrode active material.

[0037] The first layer may contain only one type of single crystal electrode active material, or may contain two or more types. The ratio of the single crystal electrode active material to all the electrode active materials contained in the first layer may be, for example, more than 50 wt %, 70 wt % or more, 90 wt % or more, or 100 wt %.

[0038] The first layer may or may not contain a polycrystalline electrode active material. In the former case, the ratio of the polycrystalline electrode active material to the total electrode active material contained in the first layer may be, for example, 1 wt % or more and less than 50 wt %, or 5 wt % or more and 40 wt % or less.

[0039] The proportion of the electrode active material layer in the first layer is not particularly limited, but is, for example, 40% by weight or more, optionally 60% by weight or more, or optionally 80% by weight or more.

[0040] The first layer may further contain a conductive material. Examples of the conductive material include carbon materials. Examples of the carbon materials include particulate carbon materials such as carbon black, and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNTs), and carbon nanofibers (CNFs). Examples of the carbon black include acetylene black (AB), ketjen black (KB), and furnace black (FB). The first layer may further contain a binder. Examples of the binder include fluorine-containing binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). The first layer usually contains an electrolyte, which will be described later.

[0041] The first layer preferably contains a fibrous carbon material as a main component of the conductive material. This is because the fibrous carbon material usually has a larger specific surface area than the particulate carbon material, and thus has good contact with the single-crystal electrode active material. The single-crystal electrode active material usually has less surface irregularities than the polycrystalline electrode active material, and therefore is less likely to have good contact with the carbon material. In contrast, by using a fibrous carbon material with a large specific surface area, the contact between the fibrous carbon material and the single-crystal electrode active material is improved, and the resistance is likely to be reduced. The ratio of the fibrous carbon material to the entire conductive material contained in the first layer may be, for example, more than 50% by weight, 70% by weight or more, 90% by weight or more, or 100% by weight.

[0042] The first layer preferably contains a first composite in which a fibrous carbon material is attached to the surface of a single crystal electrode active material. This is because the contact between the fibrous carbon material and the single crystal electrode active material is further improved. A method for producing the first composite includes a method in which the fibrous carbon material and the single crystal electrode active material are composited using a composite processing device. In the first composite, the fibrous carbon material is attached in a dispersed state to the surface of the single crystal electrode active material. The ratio of the fibrous carbon material in the first composite is, for example, 0.5% by weight or more and 5% by weight or less, and may be 1% by weight or more and 3% by weight or less. The first composite may further contain the above-mentioned binder.

[0043] The thickness of the first layer is, for example, 1 μm or more and 500 μm or less, or may be 5 μm or more and 250 μm or less, or may be 15 μm or more and 150 μm or less.

[0044] (3) Second layer The second layer in the present disclosure is a layer including a second surface of the electrode active material layer on the electrode current collector side. The second layer contains a polycrystalline electrode active material as a main component of the electrode active material.

[0045] The second layer may contain only one type of polycrystalline electrode active material, or may contain two or more types. The ratio of the polycrystalline electrode active material to all the electrode active materials contained in the second layer may be, for example, more than 50% by weight, 70% by weight or more, 90% by weight or more, or 100% by weight.

[0046] The second layer may or may not contain a single crystal electrode active material. In the former case, the ratio of the single crystal electrode active material to the total electrode active materials contained in the second layer may be, for example, 1 wt % or more and less than 50 wt %, or 5 wt % or more and 40 wt % or less.

[0047] The proportion of the electrode active material layer in the second layer is not particularly limited, but is, for example, 40% by weight or more, optionally 60% by weight or more, or optionally 80% by weight or more.

[0048] The second layer may further contain the conductive material described above. Similarly, the second layer may further contain the binder described above. In addition, the second layer usually contains an electrolyte described below.

[0049] The second layer preferably contains a particulate carbon material as a main component of the conductive material. This is because particulate carbon materials are usually cheaper than fibrous carbon materials. Polycrystalline electrode active materials usually have more surface irregularities than single-crystalline electrode active materials. Therefore, even when a particulate carbon material with a small specific surface area is used, the contact between the polycrystalline electrode active material and the particulate carbon material is good. The ratio of the particulate carbon material to the total conductive material contained in the second layer may be, for example, more than 50% by weight, 70% by weight or more, 90% by weight or more, or 100% by weight.

[0050] The second layer preferably contains a second composite in which a particulate carbon material is attached to the surface of a polycrystalline electrode active material. This is because the contact between the particulate carbon material and the polycrystalline electrode active material is further improved. The method for producing the second composite is the same as the method for producing the first composite described above. In the second composite, the particulate carbon material is attached in a dispersed state to the surface of the polycrystalline electrode active material. The proportion of the particulate carbon material in the second composite is, for example, 0.5% by weight or more and 5% by weight or less, and may be 1% by weight or more and 3% by weight or less. The second composite may further contain the binder described above.

[0051] The thickness of the second layer is, for example, 1 μm or more and 500 μm or less, and may be 5 μm or more and 250 μm or less, or 15 μm or more and 150 μm or less. The relationship between the thicknesses of the second layer and the first layer is not particularly limited, and the thickness of the second layer may be greater than the thickness of the first layer, may be the same as the thickness of the first layer, or may be smaller than the thickness of the first layer. "The thickness of the second layer and the thickness of the first layer are the same" means that the absolute value of the difference between the thicknesses of the two is 3 μm or less.

[0052] (3) Electrode active material layer The electrode active material layer in the present disclosure has at least a first layer and a second layer. The electrode active material layer may have one or more intermediate layers between the first layer and the second layer. The intermediate layer contains an electrode active material. The intermediate layer may contain, as the electrode active material, (i) only a single crystal-based electrode active material, (ii) only a polycrystalline-based electrode active material, or (iii) both a single crystal-based electrode active material and a polycrystalline-based electrode active material.

[0053] When the electrode active material layer has an intermediate layer, it is preferable that the weight ratio of the single crystal-based electrode active material in the electrode active material layer gradually decreases from the first surface to the second surface of the electrode active material layer. That is, taking the weight of all the single crystal-based electrode active materials contained in the electrode active material layer as 100 parts by weight, the weight of the single crystal-based electrode active material contained in the first layer as X parts by weight, the weight of the single crystal-based electrode active material contained in the intermediate layer as Y parts by weight, and the weight of the single crystal-based electrode active material contained in the second layer as Z parts by weight, it is preferable that X, Y, and Z satisfy X > 0, Y ≥ 0, Z ≥ 0, X > Y ≥ Z, and X + Y + Z = 100. Also, Y and Z may satisfy Y > Z.

[0054] When the electrode active material layer has an intermediate layer, it is preferable that the weight ratio of the polycrystalline-based electrode active material in the electrode active material layer gradually increases from the first surface to the second surface of the electrode active material layer. That is, taking the weight of all the polycrystalline-based electrode active materials contained in the electrode active material layer as 100 parts by weight, the weight of the polycrystalline-based electrode active material contained in the first layer as P parts by weight, the weight of the polycrystalline-based electrode active material contained in the intermediate layer as Q parts by weight, and the weight of the polycrystalline-based electrode active material contained in the second layer as R parts by weight, it is preferable that P, Q, and R satisfy P ≥ 0, Q ≥ 0, R > 0, P ≤ Q < R, and P + Q + R = 100. Also, P and Q may satisfy P < Q.

[0055] The intermediate layer in the electrode active material layer may further contain at least one of a conductive material and a binder in addition to the electrode active material. Details of the conductive material and the binder are the same as those described above, so they will not be described here. The intermediate layer usually contains an electrolyte, which will be described later. The thickness of the electrode active material layer is, for example, 2 μm or more and 1000 μm or less, and may be 10 μm or more and 500 μm or less, or may be 30 μm or more and 300 μm or less.

[0056] 2. Electrode current collector The electrode current collector in the present disclosure collects the current from the electrode active material layer. The electrode current collector may be a positive electrode current collector or a negative electrode current collector. Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. Examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon. Examples of the shape of the electrode current collector include a foil shape and a mesh shape.

[0057] B.Battery Fig. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. The battery 100 shown in Fig. 1 has a positive electrode 10, a negative electrode 20, and an electrolyte layer 30 disposed between the positive electrode 10 and the negative electrode 20. At least one of the positive electrode 10 and the negative electrode 20 corresponds to the electrode described above in "A. Electrode".

[0058] According to the present disclosure, at least one of the positive electrode and the negative electrode is the above-mentioned electrode, and therefore the battery achieves both reduced resistance and improved cycle characteristics.

[0059] 1. Positive electrode The positive electrode has a positive electrode current collector and a positive electrode active material layer disposed on the electrolyte layer side of the positive electrode current collector. The positive electrode in the present disclosure preferably corresponds to the above-mentioned electrode. On the other hand, when the positive electrode in the present disclosure does not correspond to the above-mentioned electrode, the negative electrode in the present disclosure usually corresponds to the above-mentioned electrode. In this case, any conventional positive electrode can be used as the positive electrode.

[0060] 2.Negative electrode The negative electrode has a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector on the electrolyte layer side. The negative electrode in the present disclosure preferably corresponds to the above-mentioned electrode. On the other hand, when the negative electrode in the present disclosure does not correspond to the above-mentioned electrode, the positive electrode in the present disclosure usually corresponds to the above-mentioned electrode. In this case, any conventional negative electrode can be used as the negative electrode.

[0061] 3. Electrolyte layer The electrolyte layer in the present disclosure contains at least an electrolyte, such as a liquid electrolyte (electrolytic solution), a gel electrolyte, or a solid electrolyte.

[0062] The electrolyte solution includes, for example, a lithium salt and a solvent. The lithium salt is, for example, LiPF 6 , LiBF 4 , LiClO 4 , LiAsF 6 Inorganic lithium salts such as LiCF 3 SO 3 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 C 2 F 5 ) 2 , LiC(SO 2 CF 3 ) 3 Examples of the solvent include organic lithium salts such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The solvent may be one type or two or more types.

[0063] The gel electrolyte is usually obtained by adding a polymer to an electrolytic solution. Examples of the polymer include polyethylene oxide and polypropylene oxide. Examples of the solid electrolyte include organic solid electrolytes such as polymer electrolytes; and inorganic solid electrolytes such as sulfide solid electrolytes and oxide solid electrolytes. The thickness of the electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less. The electrolyte layer may have a separator.

[0064] 4.Battery The battery in the present disclosure is typically a lithium ion secondary battery. Examples of applications of the battery include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. The battery in the present disclosure may also be used as a power source for moving objects other than vehicles (e.g., railways, ships, and aircraft), and may also be used as a power source for electrical appliances such as information processing devices.

[0065] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0066] [Synthesis Example 1] A polycrystalline positive electrode active material was synthesized according to the synthesis flow shown in Figure 4. First, NiSO 4 , CoSO 4 , MnSO 4 These were then mixed with NiSO 4 :CoSO 4 :MnSO 4 The mixture was weighed out in a molar ratio of 1:1:1 and dissolved in ion-exchanged water to a concentration of 30% by weight to obtain a raw material solution (raw material dissolution). 3A certain amount of the aqueous solution was added, and the atmosphere was replaced with nitrogen while stirring with a stirrer. NaOH was then added to adjust the pH to alkaline. While controlling the pH inside the reaction vessel at a constant level, the raw material solution and NH 3 The aqueous solution was added dropwise to precipitate the transition metal hydroxide (crystallization).

[0067] Next, the precipitated transition metal hydroxide was removed by filtration and then washed with an aqueous carboxymethyl cellulose solution (CMC solution) (washing). Next, the washed transition metal hydroxide was removed by filtration and dried at 120°C for 16 hours (drying). Next, the dried transition metal hydroxide and the Li raw material (Li 2 CO 3 ) were mixed in a mortar (Li raw material mixing). Next, the resulting mixture was fired in a muffle furnace at 800°C to 950°C for 10 hours (firing). Next, the fired product was crushed using a jet mill to obtain a positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 When the obtained positive electrode active material was observed with a scanning electron microscope (SEM), it was confirmed that the positive electrode active material was a polycrystalline positive electrode active material.

[0068] [Synthesis Example 2] The same procedure as in Synthesis Example 1 was carried out except that the firing temperature was changed to 950°C to 1100°C, and the positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 When the obtained positive electrode active material was observed with a scanning electron microscope (SEM), it was confirmed that the positive electrode active material corresponded to a single crystal type.

[0069] [Example 1] A battery was produced using the polycrystalline positive electrode active material obtained in Synthesis Example 1 and the single crystal positive electrode active material obtained in Synthesis Example 2. The battery was produced as follows. First, the single crystal positive electrode active material, conductive material (acetylene black), and binder (polyvinylidene fluoride) were weighed out in a weight ratio of single crystal positive electrode active material:conductive material:binder=88:10:2, and mixed together. A dispersion medium was added to the resulting mixture, and the mixture was stirred to obtain a positive electrode slurry for the first layer.

[0070] Next, the polycrystalline positive electrode active material, conductive material (acetylene black), and binder (polyvinylidene fluoride) were weighed out in a weight ratio of polycrystalline positive electrode active material:conductive material:binder = 88:10:2, and mixed together. A dispersion medium was added to the resulting mixture, and the mixture was stirred to obtain a positive electrode slurry for the second layer.

[0071] Next, the positive electrode slurry for the second layer and the positive electrode slurry for the first layer were continuously applied onto a positive electrode current collector (Al foil) using a film applicator (with film thickness adjustment function, All Good Co., Ltd.), and dried at 80 ° C. for 5 minutes. As a result, a positive electrode structure having a positive electrode current collector, a second layer, and a first layer was obtained. When the total amount of positive electrode active materials contained in the positive electrode active material layer was 100 parts by weight, the amount of the single crystal positive electrode active material contained in the first layer was 20 parts by weight, the amount of the polycrystalline positive electrode active material contained in the first layer was 0 parts by weight, the amount of the single crystal positive electrode active material contained in the second layer was 0 parts by weight, and the amount of the polycrystalline positive electrode active material contained in the second layer was 80 parts by weight. The active material ratio in the positive electrode active material layer was adjusted by the amount of slurry applied when the first layer and the second layer were prepared.

[0072] Next, the negative electrode active material (natural graphite) and the binder (SBR and CMC) were mixed, and a dispersion medium was added to the obtained mixture and stirred to obtain a negative electrode slurry. The obtained negative electrode slurry was applied onto a negative electrode current collector using a film applicator, and then dried at 80°C for 5 minutes. This resulted in a negative electrode structure having a negative electrode current collector and a negative electrode layer.

[0073] The positive electrode layer of the positive electrode structure and the negative electrode layer of the negative electrode structure were placed opposite each other with a separator interposed therebetween, wound, and an electrolyte was injected to obtain a battery. The electrolyte was a mixed solvent containing EC, DMC, and EMC in a volume ratio of EC:DMC:EMC=3:4:3, with LiPF 6 was dissolved to a concentration of 1M and used.

[0074] [Examples 2 and 3] A battery was obtained in the same manner as in Example 1, except that the active material ratio in the positive electrode active material layer was changed to the value shown in Table 1.

[0075] [Example 4] First, the single crystal positive electrode active material, the polycrystalline positive electrode active material, the conductive material (acetylene black), and the binder (polyvinylidene fluoride) were weighed out in a weight ratio of single crystal positive electrode active material: polycrystalline positive electrode active material: conductive material: binder = 52.8: 35.2: 10: 2, and mixed together. A dispersion medium was added to the resulting mixture, and the mixture was stirred to obtain a positive electrode slurry for the first layer.

[0076] Next, the single crystal positive electrode active material, polycrystalline positive electrode active material, conductive material (acetylene black), and binder (polyvinylidene fluoride) were weighed out in a weight ratio of single crystal positive electrode active material: polycrystalline positive electrode active material: conductive material: binder = 35.2: 52.8: 10: 2, and mixed together. A dispersion medium was added to the resulting mixture, and the mixture was stirred to obtain a positive electrode slurry for the second layer.

[0077] A battery was obtained in the same manner as in Example 2, except that the obtained positive electrode slurry for the first layer and the positive electrode slurry for the second layer were used.

[0078] [Comparative Example 1] A battery was obtained in the same manner as in Example 2, except that the positive electrode slurry for the first layer was used instead of the positive electrode slurry for the second layer.

[0079] [Comparative Example 2] A battery was obtained in the same manner as in Example 2, except that the positive electrode slurry for the second layer was used instead of the positive electrode slurry for the first layer.

[0080] [Comparative Example 3] A battery was obtained in the same manner as in Example 3, except that the positive electrode slurry for the second layer was used instead of the positive electrode slurry for the first layer, and the positive electrode slurry for the second layer was used instead of the positive electrode slurry for the first layer.

[0081] [Comparative Example 4] A single crystal positive electrode active material, a polycrystalline positive electrode active material, a conductive material (acetylene black), and a binder (polyvinylidene fluoride) were weighed out in a weight ratio of single crystal positive electrode active material: polycrystalline positive electrode active material: conductive material: binder = 44:44:10:2, and mixed together. A dispersion medium was added to the resulting mixture, and the mixture was stirred to obtain a positive electrode slurry for the first layer. The same operation was performed to obtain a positive electrode slurry for the second layer.

[0082] A battery was obtained in the same manner as in Example 2, except that the obtained positive electrode slurry for the first layer and the positive electrode slurry for the second layer were used.

[0083] [evaluation] (initial resistance) The batteries obtained in Examples 1 to 4 and Comparative Examples 1 to 4 were charged to 4.1 V and then discharged to 3.0 V. They were then charged to 3.7 V and allowed to stand at 60° C. for 9 hours. Thereafter, the charging resistance was measured at −10° C., 3.7 V, 1 C for 10 seconds to obtain the initial resistance. The results are shown in Table 1. The initial resistance in Table 1 is a relative value when Comparative Example 1 is taken as 100%.

[0084] (Capacity maintenance rate) The batteries obtained in Examples 1 to 4 and Comparative Examples 1 to 4 were charged and discharged for 200 cycles under conditions of 4.1 V to 3.0 V, 2 C, and 60° C. The capacity retention rate was calculated by dividing the discharge capacity at the 200th cycle by the discharge capacity at the 1st cycle. The results are shown in Table 1.

[0085] [Table 1]

[0086] As shown in Table 1, Examples 1 to 4 had lower initial resistance and comparable capacity retention rates compared to Comparative Example 1. In contrast, Comparative Examples 2 to 4 had lower initial resistance but significantly lower capacity retention rates compared to Comparative Example 1. Thus, it was confirmed that the present disclosure can achieve both reduced resistance and improved cycle characteristics.

[0087] [Reference example 1] The single crystal positive electrode active material produced in Synthesis Example 2, a conductive material (acetylene black, AB), and a binder (polyvinylidene fluoride) were weighed out in a weight ratio of single crystal positive electrode active material:conductive material:binder=97.5:1.5:1, and these were placed in a multipurpose small-sized mixer and grinder (MP Mixer, manufactured by Nippon Coke and Engineering Co., Ltd.) and composited at 10,000 rpm for 10 minutes to produce a first composite.

[0088] Next, the polycrystalline positive electrode active material produced in Synthesis Example 1, a conductive material (acetylene black), and a binder (polyvinylidene fluoride) were weighed out in a weight ratio of polycrystalline positive electrode active material:conductive material:binder=97.5:1.5:1, and these were placed in a multipurpose small-sized mixer and grinder (MP Mixer, manufactured by Nippon Coke and Engineering Co., Ltd.) and mixed at 10,000 rpm for 10 minutes to produce a second composite.

[0089] Next, the first composite and the second composite were mixed in a mortar for 5 minutes. The mixture obtained was formed on a positive electrode current collector (Al foil, 12 μm thick) using an electrostatic screen film forming device (manufactured by Berg Kogyo). This produced a positive electrode precursor having a positive electrode current collector and a powder layer. The production conditions were that the distance between the positive electrode current collector and the electrostatic screen was 1 cm, and a voltage of 1.5 kV was applied during film formation. Thereafter, the positive electrode precursor was sandwiched between two flat plates heated to 160°C, and a load of 15 tons was applied for 30 seconds to soften or melt the binder. This caused the powder layer to be fixed on the positive electrode current collector, and a positive electrode for evaluation was obtained.

[0090] [Reference example 2] A positive electrode for evaluation was obtained in the same manner as in Reference Example 1, except that the conductive material in the first composite was changed from acetylene black (AB) to carbon nanotubes (CNT). The first composite (using CNT) produced in Reference Example 2 and the first composite (using AB) produced in Reference Example 1 were observed by SEM. As a result, it was confirmed that the amount of CNT attached to the surface of the single crystal positive electrode active material was greater than the amount of AB attached to the surface of the single crystal positive electrode active material.

[0091] [evaluation] (electronic resistance) The electronic resistance of the evaluation positive electrodes obtained in Reference Examples 1 and 2 was measured using an electrode resistance measurement system (RM2610 manufactured by HIOKI). The results are shown in Table 2. The electronic resistance in Table 2 is a relative value when Reference Example 1 is taken as 100%.

[0092] (cell resistance) Small cells were prepared using the evaluation positive electrodes obtained in Reference Examples 1 and 2, and IV measurements were performed. Specifically, the cells were discharged for 10 seconds at currents I of 0.3C, 0.5C, and 1C, and the voltage drop ΔV was measured. The resistance (slope) was calculated from the relationship between the current I and ΔV. The results are shown in Table 2. The cell resistance in Table 2 is a relative value when Reference Example 1 is taken as 100%.

[0093] [Table 2]

[0094] As shown in Table 2, Reference Example 2 had lower electronic resistance and cell resistance than Reference Example 1. This is believed to be because the amount of conductive material (CNT) attached in Reference Example 2 was greater than the amount of conductive material (CNT) attached in Reference Example 1, and the electronic conductivity of the first composite in Reference Example 2 was greater than the electronic conductivity of the first composite in Reference Example 1. [Explanation of symbols]

[0095] 1...Positive electrode current collector 2…Positive electrode active material layer 10…Positive electrode 11…Negative electrode current collector 12…Negative electrode active material layer 20…Negative electrode 30…Electrolyte layer 100…Battery

Claims

[Claim 1] An electrode for use in a battery, comprising: The electrode has an electrode current collector and an electrode active material layer, The electrode active material layer contains, as electrode active materials, a single crystal electrode active material and a polycrystalline electrode active material, The single crystal electrode active material and the polycrystalline electrode active material are each a lithium transition metal composite oxide, the electrode active material layer has a first layer including a first surface on a side opposite to the electrode current collector, and a second layer including a second surface on the electrode current collector side, an electrode, wherein the first layer contains the single crystal electrode active material as a main component of the electrode active material, and the second layer contains the polycrystalline electrode active material as a main component of the electrode active material.

Citation Information

Patent Citations

  • Method for manufacturing positive electrode for lithium secondary battery

    JP2014139926A

  • Electrode, nonaqueous electrolyte battery and battery pack

    JP2014154317A

  • Nonaqueous electrolyte secondary battery

    JP2017195205A

  • Coating positive electrode active material

    JP2020181640A

  • Electrode and battery

    JP2023102892A